Overview of the Incidence of Post-Sectio Caesaria Back Pain with Spinal Anesthesia: A Literature Review - Putra, Agung Manik Septiana; Widnyana, I Made Gede (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2024)
Post-cesarean back pain with spinal anesthesia is one of the most common complications and can affect the patient's quality of life. Although spinal anesthesia is a safe and commonly used option in surgical procedures, the risk of back pain remains, especially if the anesthesia technique is not optimal. This study aims to provide an overview of the incidence of post-cesarean section back pain with spinal anesthesia based on a literature review over the past 10 years. This study is a literature review that reviews 10 scientific journals published in the last 10 years. The focus of this study includes the prevalence of back pain, risk factors, anesthesia techniques, and post-cesarean section back pain management. The results of the review showed that the prevalence of post-cesarean back pain ranged from 30% to 50%, with the main risk factors being age, body mass index, and anesthesia techniques. The use of smaller atraumatic needles and careful anesthesia techniques can reduce the incidence of back pain. Back pain is generally temporary, but in some patients it can develop into chronic pain. Post-cesarean section back pain with spinal anesthesia can be prevented with proper anesthesia techniques and good pain management. A multidisciplinary approach is needed to reduce the prevalence of chronic pain and improve the patient's quality of life.